2022
DOI: 10.3390/ijms231710171
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of N1,N3-Disubstituted Uracil Derivatives against SARS-CoV-2 Variants of Concern

Abstract: Despite the widespread use of the COVID-19 vaccines, the search for effective antiviral drugs for the treatment of patients infected with SARS-CoV-2 is still relevant. Genetic variability leads to the continued circulation of new variants of concern (VOC). There is a significant decrease in the effectiveness of antibody-based therapy, which raises concerns about the development of new antiviral drugs with a high spectrum of activity against VOCs. We synthesized new analogs of uracil derivatives where uracil wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…Overall, 282 participants (age, median [range], 55 [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , …”
Section: Resultsunclassified
See 1 more Smart Citation
“…Overall, 282 participants (age, median [range], 55 [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , …”
Section: Resultsunclassified
“…For instance, remdesivir, an intravenous RdRp inhibitor developed for the Ebola virus, and molnupiravir, an oral drug designed for the influenza virus, are commonly used to treat symptomatic COVID-19 patients [ 17 , 18 , 19 , 20 ]. Since in silico (computer simulations), in vitro (laboratory experiments), and in vivo (studies performed on living organisms) evidence has demonstrated the efficacy of RdRp inhibitors against SARS-CoV-2 variants, it is unsurprising that these drugs have been successful across the various waves of SARS-CoV-2 strains [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. In addition to the exploration of RdRp inhibitors as COVID-19 disease treatments, there has also been interest in using anti-RdRp agents in a prophylactic manner (i.e., to prevent disease and/or provide some protection before an exposure may occur).…”
Section: Introductionmentioning
confidence: 99%
“…The infectious virus titer in the lungs was determined as previously described [26]. Briefly, 10-fold dilutions of lung homogenates were incubated for an hour on Vero E6 cells.…”
Section: Rna Extraction and Rt-pcr Quantification Of Viral Rna Copies...mentioning
confidence: 99%
“…Siniavin et al [35] synthesised analogues of uracil derivatives substituted at N 1 and N 3 positions of the type 8 a-g. The reaction involved treatment of 1-substituted uracils 6 a-g with 4-(ω-bromoalkoxy)benzoic acid methyl esters 7 a-c dissolved in DMF in the presence of potassium carbonate to yield corresponding derivatives of uracil 8 a-g (Scheme 3).…”
Section: Introductionmentioning
confidence: 99%
“…Siniavin et al [35] . synthesised analogues of uracil derivatives substituted at N 1 and N 3 positions of the type 8 a – g .…”
Section: Introductionmentioning
confidence: 99%